Pengaruh Perendaman dengan Berbagai Konsentrasi Larutan Daun Belimbing Wuluh terhadap Kualitas Fisik Telur Itik Pegagan - Sofia Sandi; Fitra Yosi; Sarah Pratiwi; Elisahara Elisahara; Meisji Liana Sari; Riswandi Riswandi; Asmak Asmak (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Sandi S, Yosi F, Pratiwi S, Elisahara E, Sari ML, Riswandi R, Asmak A. 2020. The effect of wuluh starfruit leaves solution in different concentration to the physical quality of pegagan duck eggs. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The decrease internal of egg quality during the storage period happened because of the waste air cavity caused by evaporation of CO2 andH2O. To add more time of the egg storage period, it needs additional natural preservatives such as tannin, to block the evaporation process. The purpose of this study was to determine the effect of wuluh starfruit leaves solution in different concentration to the pH, albumin index, and yolk index of the Pegagan duck eggs. The study was conducted on March 2018 at Animal Nutrition and Feed Laboratory, Faculty of Agriculture, Sriwijaya University. This study used 72 Pegagan duck eggs and 180 grams of wuluh starfruit leaves. The experimental variable observed were egg pH, albumin index, and yolk index. This study was assigned in a Completely Random Design, which consists of 4 treatments and 6 replications. The treatments are solution with 0%, 1%, 2%, and 3% (w/v) concentration with length of storage for 14 days. Data were subjected to analysis of variance and significantly different followed by Duncan’s Multiple Range Test (DMRT) at 5%. The results showed that the level of wuluh starfruit solution up to 3% concentration had no significant effect (>0,05) to the pH, albumin index, and yolk index of the Pegagan duck eggs.